Manajemen Program Studi Independen Bersertifikat Bidang Data Analyst & Software Engineering di PT Revolusi Citra Edukasi - Oky Setiawan; Chamid Sutikno; Ariesta Amanda; Indah Ayu Permana Pribadi; Zaula Rizqi Atika (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to describe the management of the Certified Independent Study Program (SIB) in the fields of Data Analytics and Software Engineering organized by PT Revolusi Citra Edukasi. Using a qualitative approach, data were collected through participatory observation, in-depth interviews, daily activity logbooks, and documentation. Data analysis followed an interactive model consisting of data collection, data reduction, data presentation, and verification. The results reveal that the management of the SIB program is implemented through four key aspects: planning, organizing, actuating, and controlling. The planning stage includes the development of an adaptive modular curriculum, the formulation of short-term and long-term objectives, and the active involvement of industry practitioners. This stage reflects the principles of transparency, accountability, and responsibility. The organizing aspect is realized through a well-defined yet flexible organizational structure, supported by fair task distribution and clear role assignments, which embody independence, fairness, and transparency. In the actuating stage, program implementation is carried out using project-based learning methods, mentoring sessions, and active coaching. These activities are designed to ensure equitable access to guidance, transparent communication, and shared responsibility between instructors and participants. The controlling aspect involves regular digital evaluations, weekly feedback mechanisms, and collaborative assessments with industry partners, ensuring continuous improvement and adherence to program goals. Overall, the management of the SIB program at PT Revolusi Citra Edukasi demonstrates a high level of professionalism and alignment with the principles of Good Corporate Governance (GCG). The integration of adaptive planning, transparent organization, participatory implementation, and accountable evaluation processes ensures that the program not only meets its educational objectives but also fosters industry readiness among participants. These findings highlight the importance of structured yet flexible management practices in enhancing the effectiveness of independent study programs within the context of higher education and industry collaboration.